Records management practices and administration of public institutions in central equatorial state, South Sudan: a cross-sectional study. - Yanjo, Samuel Daniel; Kateregga Ali, Ali Ssalongo; Ssendagi, Mohammed (SJ Insights, 2025)
Background It is unmistakable that the pace of business activities within organizations in contemporary society is increasing daily due to evolving technology. The study aims to assess the records management practices and administration of public institutions in Central Equatorial State, South Sudan. Methodology A descriptive cross-sectional design in Central Equatorial State, Juba, South Sudan. A sample of 50 participants from Central Equatorial was used in the study. The sample was selected through a non-probability sampling technique that aimed at selecting participants from the records management department and records management champions within the organization. Results 4.17% of the respondents have 3 years and below working experience, and 37.5% of the champions have spearheaded the management of records in their departments for 3 to 6 years. 10.42% of the respondents were from the records management department. A correlation coefficient calculation reveals a 0.95, which implies a positive correlation between the variables. 81.25% agreed that indeed they experience challenges. 5 respondents indicated that they do not experience it. Conclusion Records management is an imperative element in any organization. It is through records management that the everyday activities of any organization can be accounted for. Recommendations Organizations should ascertain that the top management has the required skills, such as effective records management, and that they should act as role models for their followers